Alpheopsis balaeniceps sp. nov., an unusual alpheid shrimp (Decapoda: Caridea) from French Polynesia - Anker, Arthur (Zootaxa, 2015)
Alpheopsis balaeniceps sp. nov. is described based on a single male specimen from Moorea, French Polynesia. The new species is unique within the genus Alpheopsis Coutière, 1896 in possessing balaeniceps-type setae on the fingers of both chelipeds, being especially well developed on the major chela. Within the family Alpheidae, this feature exists only in some species of the distantly related genus Alpheus Fabricius, 1798, however, only on the minor cheliped. This convergence between Alpheopsis and Alpheus is another example of the remarkable diversity and plasticity of the alpheid chelipeds.